Design and parameter optimization of air-suction wheel type of seed-metering device with elastic pad for maize - Sun, Yuhuan; Guo, Junhai; Linrong, Shi (International Journal of Agricultural and Biological Engineering, 2024)
Due to the maize growing agronomy requires ground covered by mulch film in the arid zones of the China Northwest region, the seed-metering device must roll over, break the film, and then throw seeds into soil. However, the uneven ground can cause the seed-metering device to shake, reducing seed-metering performance. To improve the adaptability for different shapes of maize seeds, a air suction wheel type seed-metering device with elastic pad was developed for better seed extraction and bump resistance. Firstly, the advantages and influencing factors of the elastic pad were analyzed through four processes of metering seeds. Secondly, the velocity distributions of six diameters of the suction hole are compared to determine the range with FLUENT. Then, a one-factor experiment was conducted to analyze the pattern of the factors (the seed layer height, the critical vacuum, the rotational speed of the seed disk, and the suction hole diameter) influencing the metering seed performance. Finally, a five-level quadratic rotation orthogonal design was used to optimize the parameters. Results show that the optimal values are that the seed layer height is 40 mm, and the critical vacuum is 2.85 kPa, and the rotational speed of the seed disk is 20.1 r/min. The validation experiment resulted in a 93.79% qualified index, with a 4.02% missing index and a 2.19% multiple index. Key words: maize seeds; seed-metering device with air suction; elastic suction; parameter optimizationDOI: 10.25165/j.ijabe.20241704.8575Citation: Sun Y H, Guo J H, Shi L R. Design and parameter optimization of air-suction wheel type of seed-metering device with elastic pad for maize. Int J Agric & Biol Eng, 2024; 17(4): 116–127.